2023
DOI: 10.3390/nu15051265
|View full text |Cite
|
Sign up to set email alerts
|

Dietary-Derived Exosome-like Nanoparticles as Bacterial Modulators: Beyond MicroRNAs

Abstract: There is increasing evidence that food is an important factor that influences the composition of the gut microbiota. Usually, all the attention has been focused on nutrients such as lipids, proteins, vitamins, or polyphenols. However, a pivotal role in these processes has been linked to dietary-derived exosome-like nanoparticles (DELNs). While food macro- and micronutrient composition are largely well established, there is considerable interest in these DELNs and their cargoes. In this sense, traditionally, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Dietary EV uptake into the gut is dependent on EV lipid composition because the depletion of phosphatidic acid from EVs reduced uptake, whereas the addition of exogenous phosphatidic acid (34:2 and 36:4) rescued EV uptake. 39 The permeability of the gut to EVs is also reliant on LCPUFAs and LCPUFA-derived metabolites. 16,37,40 For example, AA is a precursor to biologically active eicosanoids, including prostaglandins, thromboxanes, leukotrienes, and oxylipins, which regulate permeability through physiological barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary EV uptake into the gut is dependent on EV lipid composition because the depletion of phosphatidic acid from EVs reduced uptake, whereas the addition of exogenous phosphatidic acid (34:2 and 36:4) rescued EV uptake. 39 The permeability of the gut to EVs is also reliant on LCPUFAs and LCPUFA-derived metabolites. 16,37,40 For example, AA is a precursor to biologically active eicosanoids, including prostaglandins, thromboxanes, leukotrienes, and oxylipins, which regulate permeability through physiological barriers.…”
Section: Discussionmentioning
confidence: 99%
“…To exert bioactive functions, human milk EVs must pass through barriers, including the intestine and endothelial cell lining. Dietary EV uptake into the gut is dependent on EV lipid composition because the depletion of phosphatidic acid from EVs reduced uptake, whereas the addition of exogenous phosphatidic acid (34:2 and 36:4) rescued EV uptake 39 . The permeability of the gut to EVs is also reliant on LCPUFAs and LCPUFA‐derived metabolites 16,37,40 .…”
Section: Discussionmentioning
confidence: 99%
“…A report on stomach tissues of patients with different gastric conditions, such as gastritis, metaplasia, and cancer, unveiled higher plant-derived miR-168 levels in tissues of patients affected by intestinal metaplasia [ 62 ]. In particular, the ginger-derived miR-1078, by regulating leptin, is related to lipopolysaccharide (LPS)-induced interleukin (IL)-6 expression, whereas miR-167a acts as a gut microbiota modulator targeting Lactobacillus rhamnosus GG SpaC pilus adhesin [ 63 , 64 ]. Among the different miRNAs contained in the ginger-derived exosomes-like nanoparticles (GELNs), mdo-miR-7267-3p increased the production of IL-22, thus inducing mice colitis [ 65 ], while the plant-derived miR-34a, miR-143, and miR-145 act as tumor suppressors in the mouse CRC model [ 66 ].…”
Section: Dietary Xenomirnas In Health and Diseasementioning
confidence: 99%
“…The positive effects of these alterations are not fully understood, but a vast majority of studies have shown that milk EVs can increase the abundance of beneficial bacteria while diminishing harmful bacteria in mouse models. Although the extent of these changes varies in male and female mice, a general pattern remains consistent, that these changes in microbiota will affect the intestinal level of metabolites produced by the microbiota, especially SCFAs [ 77 ], and increase intestinal epithelial absorptive cells [ 78 ]. SCFAs produced by the gut microbiota are mainly propionate, acetate, and butyrate, which not only regulate the growth of the intestinal microbial community but also provide energy for the gut microbiota and the host’s intestinal barrier cells [ 79 ].…”
Section: Microbiota Involved In and Beyond The Intestinementioning
confidence: 99%